2018
DOI: 10.1111/jam.14106
|View full text |Cite
|
Sign up to set email alerts
|

Aeromonasspp. from marketed Yesso scallop (Patinopecten yessoensis): molecular characterization, phylogenetic analysis, virulence properties and antimicrobial susceptibility

Abstract: To our knowledge, this is the first study reporting Aeromonas spp. in scallop. This implies that not only the common varieties like oysters, but other bivalves can also harbour potentially pathogenic aeromonads which may have impacts on consumer health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 51 publications
(45 reference statements)
2
27
0
Order By: Relevance
“…2018; De Silva et al . 2019). High occurrence (68%) of A. hydrophila from retailed seafood products was reported in one German study (Ullmann et al .…”
Section: Discussionmentioning
confidence: 99%
“…2018; De Silva et al . 2019). High occurrence (68%) of A. hydrophila from retailed seafood products was reported in one German study (Ullmann et al .…”
Section: Discussionmentioning
confidence: 99%
“…Ramadan et al (2018) found the occurrence of aerA (70%), ast (46%), hlyA (42%) and act (32%) from 50 examined A. hydrophila isolates in marketed mullet. De Silva et al (2019) reported the detected frequency of aerA (78%), hlyA (75%), act (75%), alt (59%) and ast (47%) among 23 Aeromonas isolates from marketed scallops. All the results showed that the prevalence rates of the same virulence gene were different in different samples, which led to a variety of virulence gene combinations.…”
Section: Tissue Samplesmentioning
confidence: 99%
“…The most reviewed virulence factors of Aeromonas sp. are aerolysin (encoded by the gene aer , similar description is suitable for other virulence factors here‐in‐after), haemolysin ( hly ), enterotoxin including labile temperature cytotoxic enterotoxin ( alt ), stable temperature cytotoxic enterotoxin ( ast ) and cytotoxic enterotoxin ( act ), temperature‐sensitive protease ( epr ), extracellular serine protease ( ahp ), serine protease ( ser ), flagellin ( fla ), lipases ( lip ), elastase ( ela ), ADP‐ribosyltransferase toxin ( aex T) and DNases ( exu ) (Li et al ; Yi et al ; Jung‐Schroers et al ; De Silva et al ). To predict the virulence strength of Aeromonas strains and its clinical symptoms, the establishment of a rapid method to distinguish virulent and nonvirulent Aeromonas strains by screening major virulence factors is needed.…”
Section: Introductionmentioning
confidence: 99%
“…2015; De Silva et al . 2019). The genus Aeromonas consists of Gram negative, facultative anaerobic, rod‐shaped bacteria (Martin‐Carnahan and Joseph 2005).…”
Section: Introductionmentioning
confidence: 99%